The Oxygen Free Radicals Originating from Mitochondrial Complex I Contribute to Oxidative Brain Injury Following Hypoxia–Ischemia in Neonatal Mice - Niatsetskaya, Zoya V. (Society for Neuroscience, 2012)
Oxidative stress and Ca(2+) toxicity are mechanisms of hypoxic–ischemic (HI) brain injury. This work investigates if partial inhibition of mitochondrial respiratory chain protects HI brain by limiting a generation of oxidative radicals during reperfusion. HI insult was produced in p10 mice treated with complex I (C-I) inhibitor, pyridaben, or vehicle. Administration of P significantly decreased the extent of HI injury. Mitochondria isolated from the ischemic hemisphere in pyridaben-treated animals showed reduced H(2)O(2) emission, less oxidative damage to the mitochondrial matrix, and increased tolerance to the Ca(2+)-triggered opening of the permeability transition pore. A protective effect of pyridaben administration was also observed when the reperfusion-driven oxidative stress was augmented by the exposure to 100% O(2) which exacerbated brain injury only in vehicle-treated mice. In vitro, intact brain mitochondria dramatically increased H(2)O(2) emission in response to hyperoxia, resulting in substantial loss of Ca(2+) buffering capacity. However, in the presence of the C-I inhibitor, rotenone, or the antioxidant, catalase, these effects of hyperoxia were abolished. Our data suggest that the reperfusion-driven recovery of C-I-dependent mitochondrial respiration contributes not only to the cellular survival, but also causes oxidative damage to the mitochondria, potentiating a loss of Ca(2+) buffering capacity. This highlights a novel neuroprotective strategy against HI brain injury where the major therapeutic principle is a pharmacological attenuation, rather than an enhancement of mitochondrial oxidative metabolism during early reperfusion.